2012 45th Hawaii International Conference on System Sciences 2012
DOI: 10.1109/hicss.2012.150
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Queries in Different Search Tasks

Abstract: The purpose of this study is to explore the characteristics of queries of varied search tasks driven by different user intents. For this, the study collected empirical and descriptive evidence of twenty-nine subjects' information searching process on the Web. Several indicators have been employed to determine different characteristics of queries. The results indicate that there were statistical differences in query iteration, identical query, failed query, clickthrough query rate among different search tasks w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…According to the different QoS requirement in the process of user queries, there are commonly two steps [20]. Because the users have not any priori knowledge of the system and they firstly want to get some understanding about the system, or the users could not insure that the search criteria was suitable for themselves.…”
Section: The Workflowmentioning
confidence: 99%
“…According to the different QoS requirement in the process of user queries, there are commonly two steps [20]. Because the users have not any priori knowledge of the system and they firstly want to get some understanding about the system, or the users could not insure that the search criteria was suitable for themselves.…”
Section: The Workflowmentioning
confidence: 99%
“…Our work falls into the former category, in contrast to important recent work, which falls into the latter category. Important recent work from the field of information retrieval are Mastora et al [21], who showed that failed queries represent 36% of overall submitted queries, and Kim and Can [16], who investigated failure as a factor characterizing queries in different search tasks. In the field of multimedia retrieval, Pu [22] compared characteristics of successful and failed image queries and Kofler et al [17] investigated video search failure search using expressions of failed user needs posted on a social forum.…”
Section: Related Work 21 Search Failurementioning
confidence: 99%